Modeling and Analysis of Energy Efficiency Parameters of Medium Pressure Boilers Using a Mixture of Natural and Blast Furnace Gases Taking into Account Air Intakes - Bezhan, Vladimir; Zhitarenko, Vladimir (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2020)
The object of this study are the thermal and energy characteristics of medium pressure boilers CHP-1, four boilers CCTI-75/39F-2-4 and two boilers TP-150-2. All boilers operate on a common steam collector 32 atm, 420 °C. Fuel is a mixture of blast furnace and natural gases in a ratio of 0.7–0.9 by volume. The characteristics of blast furnace gas are not constant: the elemental composition, humidity and dustiness of blast furnace gas change significantly. An algorithm for complex calculation of boiler characteristics and a mathematical model for optimal load distribution were developed. Theoretical volumes of combustion products were calculated, boiler efficiency and fuel consumption were determined, basic elements (furnace chamber, scallops, superheater) were calculated, joint calculation of tail heating surfaces (water economizer and air heater) with specification of exhaust gas temperature was determined and thermal balance was determined. The effect of excess air in the exhaust gases from the load was calculated. As a result of the analysis, the temperature of the exhaust gases was calculated, an indicator that characterizes the reliability and efficiency of the boiler, and the temperature at the outlet of the furnace, which characterizes the reliability of the superheater. The efficiency of the boilers was calculated and the value of the efficiency for the considered boilers was adjusted.